PERTUMBUHAN DAN PRODUKSI TANAMAN PADI DENGAN METODE SRI (SYSTEM OF RICE INTENSIFICATION) PADA BERBAGAI UMUR PINDAH TANAM BIBIT - Rifaine M.N. Erungan; Johannes E.X. Rogi; Marjam Toding; Yefta Pamandungan (Universitas Sam Ratulangi, 2015)
ABSTRACT Â This research aims to determine the effect of age on the growth and transplanting rice production by using the system of planting methods SRI ( System of Rice Intencification ) carried out in the village of Sulu District of Tatapaan for 4 months from May to September 2014. The research used randomized block design with treatment age transplanting U1 ( 0 HSS ) , U2 ( 10 HSS ) , U3 ( 15 HSS ) . Data were analyzed using the F test and continued with Least Significant Difference test level of 5 % .Â Broadcaster age transplanting significant effect on plant height and number of tillers , and no real effect on the number of productive tillers , dry grain harvest weight , 1000 grain weight , the weight of milled rice per plot , weight of dry milled grain per plant , and productivity .Â The treatment gives the best results in the production of which is the U3 treatment with seedling transplanting age 15 HSS . Keywoards : transplanting age, SRI method, rice